Economic and Social Upgrading in Global Value Chains and Industrial Clusters: Why Governance Matters - Gereffi, Gary (Journal of business ethics, 2016)
The burgeoning literature on global value chains (GVCs) has recast our understanding of how industrial clusters are shaped by their ties to the international economy, but within this context, the role played by corporate social responsibility (CSR) continues to evolve. New research in the past decade allows us to better understand how CSR is linked to industrial clusters and GVCs. With geographic production and trade patterns in many industries becoming concentrated in the global South, lead firms in GVCs have been under growing pressure to link economic and social upgrading in more integrated forms of CSR. This is leading to a confluence of “private governance” (corporate codes of conduct and monitoring), “social governance” (civil society pressure on business from labor organizations and non-governmental organizations), and “public governance” (government policies to support gains by labor groups and environmental activists). This new form of “synergistic governance” is illustrated with evidence from recent studies of GVCs and industrial clusters, as well as advances in theorizing about new patterns of governance in GVCs and clusters.